Discussion on technical countermeasure of improving development effect of low permeability reservoir - Li Xiang (E3S Web of Conferences, 2023)
Low PERMEABILITY RESERVOIR IS AN IMPORTANT MATERIAL FOUNDATION FOR STABLE PRODUCTION IN OLD AREAS, BUT DUE TO THE limitations OF reservoir physical properties, exploitation methods and other factors, the late production effect is poor, therefore, from the reservoir and development approach, the technical measures to improve oil recovery in low permeability reservoir are discussed. Based on the analysis of the factors influencing the development effect of double low reservoir and the geological characteristics of reservoir, from the viewpoint of seepage mechanics, this paper systematically classifies five indexes, such as main pipe radius, flow percentage, starting pressure gradient, clay mineral content and crude oil viscosity. The five-element combination evaluation method is used to optimize the low permeability point reservoir, and on this basis, favorable oil and gas accumulation areas are found. According TO THE DEVELOPMENT status of low permeability reservoir, reasonable injection-production network and well type are demonstrated to break the bottleneck of conventional low permeability water injection and improve the development benefit of low permeability reservoir.